FAKTOR-FAKTOR YANG MEMPENGARUHI PERNIKAHAN DI USIA MUDA DAN DAMPAK DALAM KEHIDUPAN RUMAH TANGGA DI KECAMATAN SALE DESA TENGGER - Dwi Widyaningrum; Ari Prasetyoaji (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Marriage is an agreement made by two people, a man and a woman. In this case the agreement between a man and a woman with the aim of forming a happy and eternal family must be based on the Almighty Godhead, as a religious principle in Pancasila. As well known, marriage is a physical and spiritual bond between a man and a woman who generally come from different environments, especially from their original family environment, then bind themselves to achieve a goal, namely an eternal and happy family. This research was conducted to determine the factors and impacts of young marriage. The method used is qualitative descriptive case study. Marrying at a young age has a negative impact on the family that is formed due to a lack of careful planning. It can cause problems or disputes that will occur in a household, where this young marriage has a big impact on harmony in the household. In reality, harmony is not an easy thing for every married couple to do, because married life is sometimes complicated and complex and requires carrying out responsibilities as a married couple.